Plants for human health: Almost gone but will not be forgotten - Subrata, Sumarno Adi; Perumal, John (Universitas Muhammadiyah Magelang, 2022)
Using plants to develop therapy or treatment in humans seems to be a potential way to improve patient outcomes. The continuum of plant genetics changing into foods that improve health is an applicable strategy at this present. Horticultural Science, microbial biology, bioprocessing, and nutrition sciences require during the process. Therefore, the role of healthcare professionals including medical doctors, pharmacists, and nurses is needed to discover the benefits and process them into usable objects. Establishing coordinated efforts in the evolution of the resources to address health issues and ensure a successful way with institute initiatives program. Also, clarifying and delivering information to the public can be very useful to counteract the symptoms. In addition, a need for translation research along with innovative technology will reach the objective of this issue.